Pengetahuan dan Sikap Ahli Teknologi Laboratorium Medik terhadap Standar Operasional Prosedur Penanganan Sampel Sputum - Munawaroh, Siti; Rohmah, Isna Lailatur; Kurniawan, Muhammad Rizki (Jurnal Kesehatan, 2021)
Medical Laboratory Technologist (MLT) is the medical team that examined the laboratory, including the sputum specimen, where the sputum specimen is infected that MLT must treat with care, to avoid a work accident or nosocomial infection. The purpose of this research was to find out whether there is a correlation between knowledge and attitude of MLT towards standard operating procedure (SOP) for handling Tuberculosis (TB) sputum samples. This research was conducted through an online questionnaire with a google form, where this questionnaire is filled in at the location of each MLT who works at health centers and hospitals in the Cibinong District area. Sampling techniques in the research of using purposive sampling. The research period was from June to August 2020. This research used primary data with a cross-sectional design involving 46 MLT respondents. A method of data analysis is a quantitative analysis and measured using multiple linear regression analysis. The results showed positive influence work knowledge and attitudes towards the application of SOP for handling TB sputum samples because it has the significant value of 0,012<0,05 and Fcount 4,90>Ftable 3,41 with the results of the coefficient of determination (R-square) of 0,186 (18,6%), therefore, we conclude that there is a correlation between MLT knowledge and attitudes towards the SOP of the handling TB sputum samples with a percentage of 18%.